The design of breeding programmes for stressful environments - Franklin, I.R.; Trail, J.C.M. (International Livestock Centre for Africa, 1985)
Discusses the design of breeding programmes for stressful environments. Identifies the relationship between adaptive traits and productive traits, the Development of breeding objectives and selection criteria. Includes economic objectives, heat tolerance, feed intake, disease resistance and the role of crossbreeding versus selection.